Physico-chemical composition of native fruits of the Ceará coast at different development stages - Nigéria P. Gonçalves; Eliseu M. P. de Lucena; Oriel. H. Bonilla; Francisca J. C. Tavares (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the physico-chemical composition of native fruits of the Ceará coast at different development stages. The fruits of ‘guajiru’, ‘manipuçá’, ‘murici-pitanga’ and ‘murta’ were collected during the year 2014, and the following evaluations were made: total soluble solids, total titratable acidity, pH, total soluble solids and titratable acidity ratio. A completely randomized design was used, with 5 or 6 treatments, depending on the maturation stage and 4 replicates. For total soluble solids, ‘murta’ obtained a minimum of 2.6 °Brix in stage 1 and ‘manipuçá’ obtained maximum of 24.53 °Brix in stage 5. For the total titratable acidity, ‘guajiru’ showed minimum of 0.09% in stages 3 and 4, and ‘murici-pitanga’ showed maximum of 3.29% in stage 6. ‘Murici-pitanga’ had minimum pH of 3.44 in stage 5 and ‘guajiru’, maximum pH of 5.9 in stage 2. For total soluble solids and titratable acidity ratio, ‘murici-pitanga’ exhibited a minimum of 3.25 in stages 1 and 3, and ‘guajiru’ showed maximum of 141.11 in stage 4. It was concluded that ‘guajiru’ and ‘manipuçá’ fruits reached physiological maturity in stage 3, whereas ‘murici-pitanga’ and ‘murta’ fruits reached in stage 4; thus, these are the ideal stages for fruit harvest.